EFFECTIVENESS OF WARM PAD AND ABDOMINAL STRETCHING ON REDUCING DYSMENORRHEA PAIN IN A ADOLESCENT WOMEN IN KENJERAN DISTRICT - Mahundingan, Rosari Oktaviana; Andriani, Dewi (Journal of Vocational Nursing, 2023)
Introduction: Pain during menstruation causes discomfort in daily physical activities. The study aimed to compare the effectiveness of the Warm Pad and Abdominal Stretching in reducing the dysmenorrhea pain scale. Methods: This study used a pre-experimental study design with a one-group pre-test design. This research was conducted with a total sample of 20 people with dysmenorrhea during menstruation. The sampling technique was carried out using quota sampling using a questionnaire. The statistical test used was the Wilcoxon Test with Pvalue = 0.05. Results: The Warm Pad Technique The mean value of the pain scale before the intervention was 5.5 and the average result value after the intervention was 3.3. Meanwhile, for respondents using the Abdominal Stretching Technique, the mean score for the pain scale before the intervention was 5.2 and the mean result after the intervention was 3.4. The results of processing Wilcoxon test data in the Warm Pad Technique obtained a value (p = 0.021) <0.05. So it can be concluded that the Warm Pad Technique is effective in reducing the pain scale. So it can be concluded that Abdominal Stretching is also effective in reducing the pain scale. Conclusions: The results of this study can be an alternative therapy in reducing dysmenorrhea pain which is usually applied when experiencing pain during menstruation so that the risk of pain that is felt can be neutralized.